1995
DOI: 10.1152/ajpregu.1995.268.1.r92
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 induction during exercise and heat stress in rats: role of internal temperature

Abstract: The purpose of this study was to determine if the accumulation of the 72-kDa heat shock protein (HSP70) is elevated in response to a prolonged bout of submaximal exercise in which colonic temperature (Tco) remained at control levels. Sprague-Dawley rats were randomly assigned to one of four testing groups [n = 8 per group; ambient temperatures (Ta) for each condition are included]: 1) control (cool/rest; Ta = 24 degrees C); 2) cool and exercise (cool/exercise; Ta = 14 degrees C); 3) nonexertional heating (heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
4
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 0 publications
5
123
4
1
Order By: Relevance
“…As in previous rat (Skidmore et al, 1995) and human studies (Bai et al, 2002;Huang et al, 2007;Matt et al, 2007), we used ELISA kits to measure the phosphorylated HSP contents in tissues. Our study was complemented by measuring the changes in nonphosphorylated HSP content using western blotting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in previous rat (Skidmore et al, 1995) and human studies (Bai et al, 2002;Huang et al, 2007;Matt et al, 2007), we used ELISA kits to measure the phosphorylated HSP contents in tissues. Our study was complemented by measuring the changes in nonphosphorylated HSP content using western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find data in the literature on simultaneous measurement of phosphorylated and nonphosphorylated HSPs in muscles. Indeed, most previous studies used western blotting to measure the HSP content in muscle biopsies and reported a significant HSP70 elevation in working muscle 20min (Locke et al, 1990) and 30min (Skidmore et al, 1995) after a treadmill bout in rats and 30min after an eccentric exercise in humans (Paulsen et al, 2007). ELISA measurements of plasma HSP27 and HSP70 content were performed in healthy humans and reported an early elevation of the phosphorylated HSP27 10min after maximal static handgrip (Brerro-Saby et al, 2010) and maximal cycling exercise ) while the phosphorylated HSP70 response began at 60min .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,132 HSP70 is the most highly conserved member in the HSP family and has been studied in the response to acute exercise or exercise training in animals. Brief (5 min) eccentric exercise produces no increase in HSP70 protein expression in the muscle tissue, 133 but longer and more exhaustive treadmill running 134,135 or eccentric exercise 136,137 results in a significant increase in HSP70 protein expression in cardiac and skeletal muscles. Elevated HSP70 levels are also observed in lung and kidney in response to strenuous endurance exercise.…”
Section: Exercise and Hsp70 Protein Expression In Animalsmentioning
confidence: 99%
“…The increase in strain occurring as a result of the intermittent exercise protocol can be appreciated by the early increase in HSP70 that also occurs. The increase in HSP70 is known to respond to a variety of perturbations, including exercise (40,41,56). The increase in HSP70 is also known to be involved in the protection of a range of proteins involved in such things as mitochondrial function (55) and sarcoplasmic reticulum Ca 2ϩ cycling (59).…”
Section: Perspectives and Significancementioning
confidence: 99%